2002
DOI: 10.1540/jsmr.38.153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RHC-80267, an Inhibitor of Diacylglycerol Lipase, on Excitation of Circular Smooth Muscle of the Guinea-Pig Gastric Antrum

Abstract: In small segments of circular smooth muscle isolated from the guinea-pig gastric antrum, the effects of RHC-80267, an inhibitor of diacylglycerol lipase, were investigated both on regenerative slow potentials (either occurring spontaneously or as the result of a depolarizing intracellular current injection) and on the actions of acetylcholine (ACh). As diacylglycerol is a known activator of protein kinase C (PKC), it would therefore be expected that RHC-80267 would activate PKC indirectly. In circular smooth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…The frequency of slow potentials is also sensitive to the change in membrane potential, and hyperpolarization decreases and depolarization increases the frequency until it reaches to a certain level (about 7 s interval), mainly due to refractory period for the generation of slow potentials (Nose et al, 2000;Kito et al, 2002;Suzuki et al, 2002). The present experiments indicated that the frequency of slow potentials was increased or decreased by 5-HT, with associated hyperpolarization of the membrane.…”
Section: Discussionsupporting
confidence: 49%
“…The frequency of slow potentials is also sensitive to the change in membrane potential, and hyperpolarization decreases and depolarization increases the frequency until it reaches to a certain level (about 7 s interval), mainly due to refractory period for the generation of slow potentials (Nose et al, 2000;Kito et al, 2002;Suzuki et al, 2002). The present experiments indicated that the frequency of slow potentials was increased or decreased by 5-HT, with associated hyperpolarization of the membrane.…”
Section: Discussionsupporting
confidence: 49%
“…Proteinkinase C (PKC) is one of the factors involved in the regulation of the frequency of spontaneous activity in gastric muscles, and inhibition of the activity of PKC decreases and activation increases the frequency Suzuki et al, 2002b;Lee et al, 2004;Nakamura and Suzuki, 2004a;Nakamura and Suzuki, 2004b;Suzuki et al, 2006). The present experiments showed that chelerythrine decreased the frequency of follower potentials, with no change in the amplitude and duration, and the I-D relationship shifted to the right-hand and upward direction, with no change in the slope (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…It is proposed in murine small intestine that Ca 2+ extrusion from mitochondria activates ion channels at the plasma membrane to form pacemaker potentials (Ward et al, 2000), while in the guinea-pig stomach, IP3 formation is stimulated by elevation of cytosolic Ca 2+ due to mitochondria-derived Ca 2+ release, possibly through activation of protein kinase C (Kito et al, 2002b;Suzuki et al, 2002). In both hypotheses, mitochondrial Ca 2+ handling may have a pivotal role in the production of rhythmic activity (Kito and Suzuki, 2003b).…”
Section: Discussionmentioning
confidence: 99%